Absence of Zeros for the Chromatic Polynomial on Bounded Degree Graphs - Borgs, Christian (Combinatorics, Probability and Computing, 2005)
In this paper, I give a short proof of a recent result by Sokal, showing that all zeros of the chromatic polynomial PG(q) of a finite graph G of maximal degree D lie in the disc jqj < KD, where K is a constant that is strictly smaller than 8.